A Pilot Randomized Controlled Clinical Trial Comparing Piezo Versus Conventional Rotary Surgery for Removal of Impacted Mandibular Third Molars - Joana Saraiva Amaral; Carlos Miguel Marto; João Farias; Daniela Alves Pereira; Jorge Ermida; Álvaro Banaco; António Campos Felino; Francisco Caramelo; Sérgio Matos (Bioengineering, 2022)
Background: The extraction of impacted mandibular third molars is a frequent dental surgery, interfering with patients’ quality of life. Ultrasonic surgery is an alternative to osteotomy with conventional rotary instruments. This study compares postoperative signals and symptoms after extracting impacted mandibular third molars using ultrasonic surgery or conventional rotary osteotomy. Methods: A pilot randomized controlled clinical trial was conducted. Thirty patients were randomly divided into the test group (ultrasonic technique) and a control group (conventional rotatory technique). All surgeries were timed. Swelling parameters, trismus and paraesthesia were evaluated on the day of surgery and the third, fifth and seventh postoperative days. Intraoperative bleeding was evaluated during surgery. Postoperative pain was evaluated daily by the patient through a visual analogue scale and the number of ingested analgesics. Results: Pain, swelling and trismus present beneficial results with the ultrasonic technique but without statistical significance. Intraoperative bleeding was significantly lower with ultrasonic surgery (t(28) = 3.258; p = 0.003). Operating time was significantly higher in extractions involving osteotomy and cutting crown and roots either with the conventional technique (p = 0.020) or ultrasonic technique (p = 0.039). Regardless of the surgical difficulty, no statistically significant results were detected between techniques regarding the procedure duration. Conclusions: The beneficial postoperative signs and symptoms make ultrasonic surgery a favourable therapeutic option, especially when the integrity of noble anatomical structures is the most important risk factor. Further studies with larger samples are needed to support the use of piezosurgery as a valid option for impacted mandibular third molar extraction.